Effectiveness of the contrast technique as recovery after effort according to professional athletes - da Silva, P. V. T.; Pedrini Junior, H.; de Oliveira, P. E. M.; Agostinho, J. L. P.; Castoldi, R. C.; Zanuto, E. A. C. (Fisioterapia em Movimento, 2022)
Introduction: Alterations caused in the metabolism of those who practice physical exercise regularly generate health benefits, however, in athletes, these alterations can cause muscle damage, so post-recovery recovery methods are extremely important for their physiological maintenance. Objective: To analyze the effectiveness of the contrast therapy technique with post-exercise recovery according to professional athletes. Methods: A questionnaire was applied that addressed the technical scientific knowledge of professional athletes over 18 years of age, of both sexes, about post-exerciseffort recovery techniques (PERT), personal information, and ethical issues, on an online platform. Descriptive statistical analysis was performed, with values presented in percentages and an association through the Chi-Square test on the knowledge of PERT and other independent variables. Results: In total, 63 athletes, 15 women and 48 men, answered the online questionnaire, 71.4% were between 18 and 30 years old, including swimmers, footballers, and athletics practitioners, and 85.7% had more than three years' experience in the sport and 57.1% competed at an international level. Considering the main PERTs, 92.1% were aware, 58.7% knew more than four, 96.8% frequently used at least one PERT, and 65.1% had used it for more than three years. Knowledge of PERTs is associated with age (p = 0.001), education (p = 0.001), practice time (p = 0.001), hours of daily training (0.001), and competitive level (p = 0.03). With respect to the use of the contrast technique, 36.5% of the respondents had already used it, and 34.9% found it effective. Conclusion: The athletes who used the contrast technique reported a good perception of recovery.